The relationship human resource management practices and employee’s performance / Dina Syamimi Azlang - Azlang, Dina Syamimi (Faculty of Business Management, 2017)
I am conducting a research study titled “The Relationship Human Resource Management Practices and Employee’s Performance” at Permodalan Nasional Berhad, Kuala Lumpur. Human Resource Management Practices is very important for the performance of the employees. Thus, it is also very important for the organization too. The purpose of this research is to investigate the relationship between Human Resource Management Practices and employee performance. There are three independent variables and one dependent variable in this study which are training, compensation and performance appraisal as independent variable, IV while employee performance as dependent variable, DV. I would study the relationship between each independent variables and dependent variable that is based on the result from the questionnaire that I would distribute to the 50 staff of Permodalan Nasional Berhad and analyse the results by using SPSS software.